The Effect Of Service Quality And Custumer’s Satisfaction On Custumer’s Loyality At PT. Perusahaan Perdagangan Inodonesia Branch Of Bengkulu - Nevianti Kristina; Karona Cahya Susena; Kimas Kurniawan (Penerbit Jurnal Indonesia, 2023)
The purpose of this study is determine the quality of service and customer’s satisfaction regarding customer’s loyalty for pharmaceutical products at PT. Perusahaan Perdagangan Indonesia Branch of Bengkulu. The research method used was quantitative, the sample in this study was 88 customers who purchased pharmaceutical products at PT. Perusahaan Perdagangan Indonesia Branch of Bengkulu. The sampling technique is accidental sampling technique. Data were collected using a questionnaire and the analysis methods used were multiple linear regression, determination tests and hypothesis tests. The results of the regression equation are Y = 13.225 + 0.318X1 + 0.385X2 + 3.881, meaning that service quality and customer’s satisfaction have an influence on customer’s loyalty at PT. Perusahaan Perdagangan Indonesia Branch of Bengkulu. The determination test result is 0.396, meaning that service quality and customer’s satisfaction have an effect on employee customer’s loyalty at PT. Perusahaan Perdagangan Indonesia Branch of Bengkulu by 39.6%, while the remaining 60.4% is explained or influenced by other variables that were not studied. Service quality and customer’s satisfaction together. has the same effect on customer’s loyalty at PT. Perusahaan Perdagangan Indonesia Branch of Bengkulu with a significance value of 0.000, less than 0.05. Service quality has a positive and significant effect on customer’s loyalty at PT. Perusahaan Perdagangan Indonesia Branch of Bengkulu, because the significance value of 0.000 is less than 0.05. Customer’s satisfaction has a positive and significant effect on customer’s loyalty at PT. Perusahaan Perdagangan Indonesia Branch of Bengkulu, with a significance value of 0.000, which is less than 0.05.